Best practice in alien species risk assessment: a comment on Leung et al. (2012). (23rd August 2013) - Barry, Simon C; Rejmanek, Marcel
Abstract The TEASI model is presented in Leung et al. (2012; TEASIng apart alien species risk assessments: a framework for best practices. Ecol. Lett., 15, 1475) as a framework for best practice in alien species risk assessment. This is not supported by the paper's review as it does not define good, bad or best practice and therefore cannot logically make this claim.